Issues of Police’s Informal Economic Activity: Studies of Police Corruption in Developed, Developing Countries and Countries in Transition - Алексей Игоревич Изюмов; Леонид Янович Косалс (Journal of Economic Sociology, 2010)
The paper analyzes the methodological and empirical research on issues of informal economic activity of the police in the developed and developing countries and countries with transition economies. The focus is set on reasons, mechanisms and practices of police corruption. The comparative analysis of the indicated types of countries demonstrates that the origination of corruption is many-faceted. The police corruption in the developed countries contrasts with that in the developing and transition countries. Moreover, these diversities shed light upon the scales and forms of police corruption in the developing and transition countries, and upon the necessary tools to reduce it.